Cationic Copolymer‐Chaperoned 2D–3D Reversible Conversion of Lipid Membranes. Issue 44 (24th September 2019) - Shimada, Naohiko; Kinoshita, Hirotaka; Umegae, Takuma; Azumai, Satomi; Kume, Nozomi; Ochiai, Takuro; Takenaka, Tomoka; Sakamoto, Wakako; Yamada, Takayoshi; Furuta, Tadaomi; Masuda, Tsukuru; Sakurai, Minoru; et al.
Abstract: Nanosheets have thicknesses on the order of nanometers and planar dimensions in the micrometer range. Nanomaterials that are capable of converting reversibly between 2D nanosheets and 3D structures in response to specific triggers can enable construction of nanodevices. Supra‐molecular lipid nanosheets and their triggered conversions to 3D structures including vesicles and cups are reported. They are produced from lipid vesicles upon addition of amphiphilic peptides and cationic copolymers that act as peptide chaperones. By regulation of the chaperoning activity of the copolymer, 2D to 3D conversions are reversibly triggered, allowing tuning of lipid bilayer structures and functionalities. Abstract : 3D lipid vesicles are converted to 2D lipid nanosheets by addition of anionic amphiphilic peptides and cationic copolymers that act as peptide chaperones. 2D–3D reconversion is triggered by stimuli such as enzymatic activity or pH change, allowing tuning of lipid bilayer structures and functionalities.